Removal of Fluoride by Using Coconut Shell Charcoal and Paddy Husk Charcoal - Santhi, D. (Asian Journal of Chemistry, 2010)
The removal of fluoride by using coconut shell charcoal and paddy husk charcoal is described. The results showed that these adsorbents are effective defluoridating agents but cannot be applied for commercial purposes.